2003
DOI: 10.1021/jf030030w
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Plant Sterol and Stanol Esters in Cholesterol-Lowering Spreads and Beverages Using High-Performance Liquid Chromatography−Atmospheric Pressure Chemical Ionization−Mass Spectroscopy

Abstract: Plant sterol and stanol esters were separated on a Luna hexyl-phenyl column using a gradient of acetonitrile (90-100%) in water. The eluted compounds were detected by atmospheric pressure chemical ionization (APCI)-mass spectroscopy (MS) in the positive mode. Sterol and stanol esters produced [M + H - HOOCR](+) ions. Application of the hyphenated technique-LC-MS-allowed differentiation between a number of esters of sitosterol, campesterol, stigmasterol, and (tentatively) avenasterol, as well as sitostanol and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 18 publications
0
23
1
Order By: Relevance
“…In two studies with orange juices, samples enriched with esterified PS (Mezine et al, 2003) (PS origin not specified) and PS from vegetable oils (Devaraj, Jialal, & Vega-López, 2004), a PS profile in which the predominant representative was β-sitosterol (40-50%) in a proportion lower than that found in our study (see Table 2) was reported. The percentage ranges in turn obtained for stigmasterol and campesterol were 20-23% and 25-27%, respectively, which were far higher than the levels recorded in our samples.…”
Section: Determination Of Plant Sterolscontrasting
confidence: 79%
See 1 more Smart Citation
“…In two studies with orange juices, samples enriched with esterified PS (Mezine et al, 2003) (PS origin not specified) and PS from vegetable oils (Devaraj, Jialal, & Vega-López, 2004), a PS profile in which the predominant representative was β-sitosterol (40-50%) in a proportion lower than that found in our study (see Table 2) was reported. The percentage ranges in turn obtained for stigmasterol and campesterol were 20-23% and 25-27%, respectively, which were far higher than the levels recorded in our samples.…”
Section: Determination Of Plant Sterolscontrasting
confidence: 79%
“…Plant sterol content has been determined in several milk beverages enriched with free or esterified PS (Laakso, 2005;Menéndez-Carreño et al, 2008;Saraiva, Castilho, Martins, Noronha da Silveira, & Ramos, 2011;Soupas et al, 2006), and in orange juices fortified with sterol esters (Mezine, Zhang, Macku, & Lijana, 2003) and with a sterol concentrate (Clement, Hansen, Costin, & Perri, 2010). However, few studies to date have identified and quantified POPs in other foods, and the existing publications mostly focus on high lipid content matrixes (Bortolomeazzi, Cordano, Pizzale, & Conte, 2003;Dutta, 2002;Soupas, Huikko, Lampi, & Piironen, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…SRM increases selectivity, but more than one transition is needed for reliable confirmation, which preferable is combined with other evidence such as relative intensities of product ions in the mass spectra, accurate mass, retention time and peak shape to positively identify the compound as vitamin D (Jäpelt et al, 2011b). LC-MS and LC-MS/MS have also been used several times for analysis of sterols in plant matrices (Mezine et al, 2003; Rozenberg et al, 2003; Ruibal-Mendieta et al, 2004; Cañabate-Díaz et al, 2007; Lu et al, 2007; Jäpelt et al, 2011b). To study vitamin D and its sterol precursors in plants LC-MS/MS is the method of choice.…”
Section: Analytical Methods To Study the Vitamin D Forms In Plantsmentioning
confidence: 99%
“…In this way, information regarding the fatty acid composition of the steryl esters is lost. Approaches for the analysis of intact esters have also been reported (Barnsteiner, Lubinus, di Gianvito, Schmid, & Engel, 2011;Caboni, Iafelice, Pelillo, & Marconi, 2005;Gordon & Griffith, 1991;Gunawan, Melwita, & Ju, 2010;Kamm et al, 2001;Mezine, Zhang, Macku, & Lijana, 2003).…”
Section: Introductionmentioning
confidence: 99%